∛-192 = ∛(-1*64*3) = -1*4*∛3
-6∛13) = ∛((-6)^3*13) = ∛(-216)(13) = ∛-2808
Convert each mixed radical to an entire radical and each entire radical to the simplest mixed radical.
1.) ^3 root -192
The answer is -4 exponent 3root 3 but I can't figure out how to get the answer.
2.) -6 exponent 3root 13
The answer is exponent 3 root -2808, but I can't figure out how to get the answer.
2 answers
not sure of your notation.
does ^3 root -192 supposed to mean
the cuberoot of -192 ?
if so , (-192)^(1/3)
= (-64)^(1/3) * (3^(1/3)
= -4 (3)^(1/3) or -4 cuberoot (3)
-6 exponent 3root 13 ??
= (-6)^3 √13 ???
does ^3 root -192 supposed to mean
the cuberoot of -192 ?
if so , (-192)^(1/3)
= (-64)^(1/3) * (3^(1/3)
= -4 (3)^(1/3) or -4 cuberoot (3)
-6 exponent 3root 13 ??
= (-6)^3 √13 ???